2017
DOI: 10.1302/0301-620x.99b7.bjj-2016-0767.r2
|View full text |Cite|
|
Sign up to set email alerts
|

A pragmatic randomised controlled trial comparing the efficacy of a femoral nerve block and periarticular infiltration for early pain relief following total knee arthroplasty

Abstract: AimsThe aim of this study was to compare the effectiveness of a femoral nerve block and a periarticular infiltration in the management of early post-operative pain after total knee arthroplasty (TKA).Patients and MethodsA pragmatic, single centre, two arm parallel group, patient blinded, randomised controlled trial was undertaken. All patients due for TKA were eligible. Exclusion criteria included contraindications to the medications involved in the study and patients with a neurological abnormality of the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
0
15
0
5
Order By: Relevance
“…including 10 studies with 950 patients, showed that LIA was as effective as FNB in terms of visual analog scale score for pain control at 24/48/72 h, total morphine consumption, range of motion, knee society score, complications, and length of hospital stay. Wall et al . performed an RCT and demonstrated that the patients with LIA used less morphine in the first postoperative day after TKA compared with the patients with FNB.…”
Section: Intraoperative Analgesic Regimensmentioning
confidence: 99%
“…including 10 studies with 950 patients, showed that LIA was as effective as FNB in terms of visual analog scale score for pain control at 24/48/72 h, total morphine consumption, range of motion, knee society score, complications, and length of hospital stay. Wall et al . performed an RCT and demonstrated that the patients with LIA used less morphine in the first postoperative day after TKA compared with the patients with FNB.…”
Section: Intraoperative Analgesic Regimensmentioning
confidence: 99%
“…After full-text review of the remaining 475 articles, 2 papers (Thienpont [2014] 10 and Wall et al [2017] 11 ) that described PPI were included in our review (Table I). These 2 papers accounted for a total of 380 patients.…”
Section: Identifying Relevant Articlesmentioning
confidence: 99%
“…A recent study comparing LIA (levobupivacaine 150 mg, 30 mg ketorolac, 10 mg morphine, and 0.25 mg adrenaline) to FNB showed similar pain control in both groups. 33 Given that the levobupivacaine dose is half of that used in this study, the comparison of FNB with GTX 2/3 should be interesting to investigate.…”
Section: Discussionmentioning
confidence: 99%